2021
DOI: 10.1097/gme.0000000000001849
|View full text |Cite
|
Sign up to set email alerts
|

A predictive model of choosing pessary type for women with symptomatic pelvic organ prolapse

Abstract: Objective: To investigate clinical factors including translabial ultrasound parameters, which are predictive for choosing pessary type (Ring or Gellhorn) in the fitting trial, and to establish a predictive model. Methods: A retrospective study was conducted on symptomatic women with pelvic organ prolapse (POP) at the Pelvic Floor Disease Diagnosis and Treatment Center (Liaoning Province, China) between May 2018 and December 2020 who were successfully fitted with pessari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
1
1
0
Order By: Relevance
“…In terms of improving the effective rate of cystocele, the PFMT + P group (43.3%) was significantly better than the other 2 groups (15.6% and 25.9%); for most patients, half or more of the above 3 groups maintained their original prolapse state (Ba point remained roughly unchanged); only a small number of patients experienced further exacerbation of prolapse. From the corresponding ultrasound indicators, we found that the improvement of ΔBSD in the PFMT + P group was more obvious, which was consistent with the improvement trend of POP in physical examination, and also reflects the consistency of 2 detection methods for evaluating the stage of prolapse (Ba point in POP-Q system and numerical description of BSD in ultrasound examination) ( 16 ). Compared with other reported figures ( 17 - 20 ), prolapse-specific symptoms reduced significantly in the patients of the PFMT + P group, measured by the PFDI-20 at 6 and 12 months, which may be related to the direct improvement of cystocele and restoration of bladder urination function by the uterine support from the perspective of physical support.…”
Section: Discussionsupporting
confidence: 67%
“…In terms of improving the effective rate of cystocele, the PFMT + P group (43.3%) was significantly better than the other 2 groups (15.6% and 25.9%); for most patients, half or more of the above 3 groups maintained their original prolapse state (Ba point remained roughly unchanged); only a small number of patients experienced further exacerbation of prolapse. From the corresponding ultrasound indicators, we found that the improvement of ΔBSD in the PFMT + P group was more obvious, which was consistent with the improvement trend of POP in physical examination, and also reflects the consistency of 2 detection methods for evaluating the stage of prolapse (Ba point in POP-Q system and numerical description of BSD in ultrasound examination) ( 16 ). Compared with other reported figures ( 17 - 20 ), prolapse-specific symptoms reduced significantly in the patients of the PFMT + P group, measured by the PFDI-20 at 6 and 12 months, which may be related to the direct improvement of cystocele and restoration of bladder urination function by the uterine support from the perspective of physical support.…”
Section: Discussionsupporting
confidence: 67%
“…Urogynaecology nurse specialist should be able to fit the pessaries and change them and identify any ulceration and bleeding caused by pessary use. The nurse led pesky clinic in primary and secondary care is a well established model and proved to be cost effective and reduces patient loads on the outpatients clinics with high patient satisfaction rate [34].…”
Section: Pessary Managementmentioning
confidence: 99%